A facility-location model for biofuel plants: Applications in the Colombian context - Duarte, Alexandra E.; Sarache, William A.; Costa, Yasel J. (Energy (Oxford), 2014)
To reduce the logistical and operating costs for biofuel plants, it is important to make a strategic decision to select the proper site for a new facility. Due to the facility's complexity, the facility-location problem must consider the supply-chain structure, involving the material flow from suppliers to customers. This paper proposes an optimisation framework that combines the process design and configuration of the supply chain using an MILP (mixed-integer linear programming) formulation. The model was applied to locate a second-generation bioethanol plant in Colombia that uses an agricultural residue known as Coffee-CSs (coffee cut stems). The experimental results indicate that placing a processing plant at Ibagué city results in the best profitability. A post-optimisation analysis indicated that even for a long period, the location decision did not change. •An optimisation model to locate biofuel-processing plants is presented.•The model integrates the process design and the supply chain optimisation.•The optimisation process was developed using a feedstock called coffee cut stems.•A sensitivity analysis is presented in order to estimate the variation of benefits.